AKURASI ARAH KIBLAT DI PEEMAKAMAN BERGOTA 2 KEMBANGRUM KOTA SEMARANG - Firza Baihaqi Ibnu Faizal; Karmila, Bilqos Nurull; Wahbi, Mudrika (ELFALAKY: Jurnal Ilmu Falak, 2024)
The direction of the Qibla is something that is often a hotly debated issue in the Islamic world. Because the distance between countries varies, which then also influences the difference in degrees of Qibla direction, a Qibla direction accuracy test is needed. Not only when performing worship, but there is also a series of Islamic laws which require facing the direction of the Qibla, for example when burying a body. This research aims to find out how far the deviation from the Qibla direction occurs at TPU Bergota 2 Kembangarum Semarang. The method used in this research is a descriptive qualitative approach in the nature of field research. From the results of this research, it was found that TPU Bergota 2 Kembangarum Semarang had a deviation of around 12° 12' 43.15". Based on the results of research that has been carried out regarding the accuracy of the Qibla direction at the Bergota 2 Kembangarum Cemetery in Semarang using several methods of Qibla direction accuracy using astronomical instruments such as theodolite, istiwa'aini, and rashdul Qibla, it is concluded that this location has a coordinate point of approximately –7° 0' 57” LS and 110° 22' 47” BT.